Narratives of the Islamic conquest from medieval Spain - Hazbun, Geraldine (New Middle Ages (Palgrave (Firm)), 2015)
Exploring medieval literary representations of the Islamic conquest of Spain in 711, Hazbun discusses chronicles, epic and clerical poetry, and early historical novels. While material on the conquest of Spain is substantial, it is understudied and this book works to fill that gap.